Multiple Treatment Meta-Analysis of Intra-Articular Injection for Temporomandibular Osteoarthritis - Liu, Yan; Wu, Jia-shun; Tang, Ya-ling; Tang, Ya-jie; Fei, Wei; Liang, Xin-hua (Journal of oral and maxillofacial surgery, 2020)
The purpose of the present study was to compare the efficacy of intra-articular injections of different agents for temporomandibular osteoarthritis (TMJOA) using a network meta-analysis. A comprehensive search strategy was performed in multiple English and Chinese language electronic databases. Randomized controlled trials comparing the effect of intra-articular injections of different agents to treat TMJOA were included in accordance with the inclusion and exclusion criteria. The bias of risk in each study was assessed, with data extraction performed independently by 2 reviewers. The primary outcomes included pain intensity and maximal mouth opening. A total of 11 trials were included in the present study, and 10 different agents (ie, hyaluronic acid, dexamethasone, prednisolone, betamethasone, betamethasone plus hyaluronic acid, morphine, tramadol, platelet-derived growth factor [PDGF], placebo, arthrocentesis alone) administered using intra-articular injections were assessed. The evidence from the direct comparisons showed that arthrocentesis plus sodium hyaluronate resulted in significantly better pain relief outcomes compared with arthrocentesis alone. Also, the visual analog scale score was further reduced to 1.27 by PDGF injection after arthrocentesis (arthrocentesis plus PDGF) compared with arthrocentesis alone. Morphine and tramadol had a high probability of being the best treatment for pain control, with PDGF ranked third. When considering pain relief, arthrocentesis plus sodium hyaluronate resulted in a better outcome than arthrocentesis alone, and arthrocentesis plus PDGF was better than arthrocentesis plus placebo. PDGF injections had the greatest probability of being the best treatment for improving joint opening, followed by sodium hyaluronate. Tramadol, morphine, and PDGF injections after arthrocentesis were effective in the treatment of TMJOA with excellent effects in reducing pain and improving joint opening. Hyaluronic acid injections were effective for improving the maximal mouth opening of patients with TMJOA in the short-term. The combination of a corticosteroid and hyaluronic acid injection reduced the symptoms of TMJOA more than corticosteroid injections alone, but not of hyaluronic acid alone.